The assessment and management of credit risk of commercial banks - Viktoria V. Borisova, Elena E. Panfilov,; Alexander E. Ushanov, Lev N. Demidov,; Alexander E. Ushanov, Lev N. Demidov,; Maramygin, Maksim S. (Opción, 1970)
This paper discusses methods for assessing and managing the credit risk of commercial banks in the context of Nassim Taleb’s works via comparative qualitative research methods. As a result, Taleb does not offer strategies for negative events, while emphasizing that luck is the main factor for success, and not purposeful, daily, painstaking work. In conclusion, such an approach may be possible for use in the short term, while for long periods of time it is advisable to introduce traditional methods based on the methods of mathematics and statistics into the assessment.